Sympathetic neural responses to mental stress during acute simulated microgravity - Durocher, John J. (American Physiological Society, 2009)
Neural and cardiovascular responses to mental stress and acute 6° head-down tilt (HDT) were examined separately and combined. We hypothesized sympathoexcitation during mental stress, sympathoinhibition during HDT, and an additive neural interaction during combined mental stress and HDT. Muscle sympathetic nerve activity (MSNA), mean arterial pressure (MAP), and heart rate (HR) were recorded in 16 healthy subjects (8 men, 8 women) in the supine position during three randomized trials: 1) mental stress (via mental arithmetic), 2) HDT, and 3) combined mental stress and HDT. Mental stress significantly increased MSNA (7 ± 1 to 12 ± 2 bursts/min; P < 0.01), MAP (91 ± 2 to 103 ± 2 mmHg; P < 0.01), and HR (70 ± 3 to 82 ± 3 beats/min; P < 0.01). HDT did not change MSNA or HR, but MAP was reduced (91 ± 2 to 89 ± 3 mmHg; P < 0.05). Combined mental stress and HDT significantly increased MSNA (7 ± 1 to 10 ± 1 bursts/min; P < 0.01), MAP (88 ± 3 to 99 ± 3 mmHg; P < 0.01), and HR (70 ± 3 to 82 ± 3 beats/min; P < 0.01). Increases in MSNA and HR during the combination trial were not different from the sum of the individual trials. However, the increase in MAP during the combination trial was significantly greater than the sum of the individual trials (change of 11 ± 1 vs. 9 ± 1 mmHg; P < 0.05). We conclude that the interaction for MSNA and HR are additive during combined mental stress and HDT but that MAP responses are slightly augmented during the combined trial. These findings demonstrate that sympathetic neural responses to mental stress are unaltered by simulated microgravity.